An interactive decision support method for real estate management in a multi-criteria framework – REMIND - Taillandier, Franck; Abi-Zeid, Irène; Taillandier, Patrick; Sauce, Gérard; Bonetto, Régis (International Journal of Strategic Property Management, 2014)
Managing a housing stock involves complex decision making such as the design of a multiyear action plan pertaining to the maintenance and upgrading of the properties. In order to address this problem, we developed a novel interactive decision support method (REMIND) to assist a housing stock manager in the progressive design and choice of a multiyear action plan based on multiple criteria. It uses a filtering approach both at the individual action level and at the global scenario level where the housing stock manager can gradually express preferences and conduct what-if analyses. An optimization component based on Tabu search allows the decision-maker to obtain a set of good plans from which he can choose the one to implement. The quality of a plan is defined in terms of how well it meets the goals on each criterion. The application of the method was tested in a leading French property management company. First Publish Online: 18 Sep 2014